P31 - Prevalence of cardiovascular disease risk factors in a Nepalese post-seismic population: a comparative study using propensity score matching. (Journal of Statistics on Health Decision, 2019)
Non-communicable disease are the leading causes of death in developed and developing countries worldwide (1). Nepal is an example of this paradigm - from 2005 to 2015, the ischemic heart disease increased around 25.3% and brain vascular disease increased 25.7%. (2) The April and May 2015 earthquakes imposed critical social and epidemiological pressures, resulting in critical lifestyle changes, namely regarding cardiovascular disease (CVD) risk factors.(3) Various organisations provided support to these people and engaged in various activities aiming to opportunistically improve this CVD burden.The aim of this study was to appraise the prevalence of CVD risk factors and health behaviours in two cohorts of a native Nepalese population, with a common origin from a remote village that were separated in two groups after the incidents of the May 2015 earthquake, using a Propensity Score Matching (PSM) analysis.
Keywords: cardiovascular disease risk factors, propensity scores matching, health behaviors